A landscape of X-inactivation during human T-cell development in the thymus - Ekwall, Olov (University of Gothenburg, 2022)
The aim of the study was to investigate X-inactivation during human T-cell development in the thymus. Thymocytes from six different developmental stages from seven individuals were isolated and studied regarding gene expression. The data set contains data from RNA sequencing, DNA methylation and whole exome sequencing.

The dataset contains data from the manuscript "A landscape of X-inactivation during human T-cell development in the thymus" by Gylemo et al, and consists of results from RNA sequencing (fastq.gz), analysis of DNA methylation (Grn.idat) and whole exome DNA sequencing (fastq.gz) of six developmental stages of thymocytes from seven individuals.

The data is described on individual and cell-type level in the tab-separated metadata files (.tsv).
MD5 checksums for each file are included.

Huvudsyftet med studien har varit att studera X-inaktivering under T-cellsutveckling i human thymus. I studien har sex olika utvecklingsstadier av thymocyter isolerats från sju individer och studerats avseende genuttryck. Datamaterialet innehåller data från RNA-sekvensering, DNA-metylering och helexom-sekvensering av DNA.

Datasetet innehåller data från manuskriptet "A landscape of X-inactivation during human T-cell development in the thymus" av Gylemo et al och innehåller resultat från RNA-sekvensering (fastq.gz), analys av DNA-metylering (Grn.idat) och DNA-exomsekvensering (fastq.gz) av sex olika mognadsstadier av thymocyter från totalt sju individer.

Data är beskrivna på individ- och celltypsnivå i de bifogade tabbseparerade metadatafilerna (.tsv).
Kontrollsummor i MD5-format för datafilerna finns tillgängliga.
X-inaktivering under T-cellsutvecklingen i thymus
Keywords: Hemic and Immune Systems; Blod- och immunsystem; Immune System; Immunsystem; Cardiovascular Surgical Procedures; Kardiovaskulära kirurgiska ingrepp; T-Lymphocytes; T-lymfocyter; Thymus Gland; Bräss; Thymocytes; Tymocyter; Immunology in the Medical Area; Immunologi inom det medicinska området